2013
DOI: 10.3171/2013.3.jns121950
|View full text |Cite
|
Sign up to set email alerts
|

Impact of global cerebral atrophy on clinical outcome after subarachnoid hemorrhage

Abstract: Object Atrophy in specific brain areas correlates with poor neuropsychological outcome after subarachnoid hemorrhage (SAH). Few studies have compared global atrophy in SAH with outcome. The authors examined the relationship between global brain atrophy, clinical factors, and outcome after SAH. Methods This study was a post hoc exploratory analysis of the Clazosentan to Overcome Neurological Ischemia and Infarction Occurring After Subarachnoid Hemorrhage (CONSCIOUS-1) trial, a randomized, double-blind, placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…This is consistent with studies in humans with SAH that show that cognitive dysfunction may be associated with temporal lobe volume loss in the absence of infarctions. 3,20 Animal studies in models of traumatic brain injury also found memory impairment in the absence of hippocampal cell death. 25 Role of Key Proteins in Long-Term Potentiation Enhanced expression of phosphorylated GluR1 by CamK-II is a key molecular event for induction and maintenance of LTP.…”
Section: New Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with studies in humans with SAH that show that cognitive dysfunction may be associated with temporal lobe volume loss in the absence of infarctions. 3,20 Animal studies in models of traumatic brain injury also found memory impairment in the absence of hippocampal cell death. 25 Role of Key Proteins in Long-Term Potentiation Enhanced expression of phosphorylated GluR1 by CamK-II is a key molecular event for induction and maintenance of LTP.…”
Section: New Findingsmentioning
confidence: 99%
“…1 Brain magnetic resonance imaging (MRI) of patients after SAH shows that there may be atrophy in the medial temporal lobes and that this may correlate with neurocognitive deficits in the absence of any focal structural lesions. 2,3 The hippocampal formation in the medial temporal lobe has been postulated to be involved in cognitive functions such as learning and memory. Long-term potentiation (LTP), a form of synaptic plasticity, is believed to be a cellular substrate of memory and learning.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the mouse perichiasmatic injection model used by Sabri et al [29, 36], they observed a significant increase of microthrombosis in both the hippocampus and cerebral cortices. Although brain injury due to aneurysmal SAH causes global parenchymal damage [37, 38], vulnerability to subcortical brain regions may differ [39]. This might explain the SAH-induced significant increase of microthrombosis in the rabbit brain parenchyma at the hippocampal levels but not the cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The overall correlation of poor outcome with advancing age has been partially explained by some factors, such as mRS scores at onset [19], brain atrophy [20], poor neurological grade at admission [21], increased amount of blood on CT, and preexisting medical diseases [8]. The greater incidence of poor outcome in elderly patients is multifactorial, and symptomatic vasospasm is probably just one of the factors involved in poor outcome.…”
Section: Discussionmentioning
confidence: 99%